Review article: adherence to Rome criteria in therapeutic trials in functional dyspepsia. Issue 5 (24th July 2014) - Stanghellini, V.; Cogliandro, R.
Summary Background The Rome criteria are currently required by health authorities for the inclusion of patients affected by functional dyspepsia in therapeutic trials. However, the degree of adherence to these criteria has not been formally verified. Aim To review adherence to the Rome criteria for inclusion criteria, outcome measures and endpoints in therapeutic trials on functional dyspepsia and the potential impact on the conclusions that can be drawn from these studies. Methods A total of 1818 articles were screened. Fifty‐eight trials claiming to include adults affected by functional dyspepsia as defined by the Rome criteria published as full articles in English between 2000 and 2013 were considered. Results Lack of full adherence to the Rome criteria of inclusion criteria was found in 54% of the studies, due to inclusion of patients with symptoms not reported in the Rome criteria or definitions of dyspeptic symptom that varied from those proposed by the Rome criteria. Ninety‐five per cent of clinical trials adopted therapeutic outcome measures that were not adherent to the Rome criteria, using questionnaires that did not include all dyspeptic symptoms or including symptoms other than those proposed by the Rome criteria. Conclusions Stringent criteria have not been adopted for inclusion criteria and outcome measures in the vast majority of published studies on functional dyspepsia that claim to have been carried out according to the Rome criteria. Appropriate questionnaires should be developed to promote adherence to internationally accepted definitions of the syndrome in future studies.